Agraryści chorwaccy w walce o niepodległość oraz demokratyczno-ludowy i federacyjny kształt Królestwa Serbii, Chorwacji, Słowenii (1904–1922) - Turkowski, Romuald (Zeszyty Wiejskie, 2016)
The article presents the circumstances of the creation, at the beginning of the twentieth century, of the Croatian Peasants Party. It emphasizes that its founders, and then leaders, Dr Stepan Radić and his brother Antun Radić, were part of the group of prominent representatives of the peasant class, who, having obtained an education and a higher position in life did not forget the social stratum from which they came and decided to gain for that class an appropriate position in society and the nation. The Radić brothers together with their colleagues, including Dr Vladko Maciek, entered the inner circle of the leaders of peasant Central Eastern and Southern Europe that were embarking on such a plan. Dr S. Radić became an distinguished leader and the political ideologue of the peasant movement in this part of Europe, along with Antonin Svehla from the Czech Republic, Dr Milan Hodza from Slovakia, Alexander Stamboliyski from Bulgaria, Wincenty Witos from Poland and Dr Iuliu Maniu from Romania. The article focuses on the struggle of Dr S. Radić, as the leader of the Croatian Peasant Party, for the democratic, federal and just shape of the Kingdom of the Serbs, Croats, and Slovenes in 1918–1922. Dr S. Radić and his Croatian Peasants Party had a significant impact on improving the political and economic situation of Croatian peasants, and also that of Serbian and Slovenian peasants, in this newly created Kingdom of the South Slavs.